Magneto-Active Polymers : Fabrication, characterisation, modelling and simulation at the micro- and macro-scale - Pelteret, Jean-Paul; Steinmann, Paul (De Gruyter, 2019)
From fabrication to testing and modeling this monograph covers all aspects on the materials class of magneto active polymers. The focus is on computational modeling of manufacturing processes and material parameters. As other smart materials, these elastomers have the ability to change electrical and mechanical properties upon application of magnetic fields. This allows for novel applications ranging from biomedical engineering to mechatronics.